2018
DOI: 10.1111/cxo.12541
|View full text |Cite
|
Sign up to set email alerts
|

Intense pulsed light treatment and meibomian gland expression for moderate to advanced meibomian gland dysfunction

Abstract: Background:The aim was to evaluate the efficacy of periocular intense pulsed light therapy combined with meibomian gland expression for chronic dry eye due to moderate to advanced meibomian gland dysfunction. Conclusions: Serial intense pulsed light therapy combined with meibomian gland expression significantly improved dry eye symptoms and clinical signs, including meibomian gland secretion quality and expressibility and ocular surface inflammation. Treatment effects were cumulative and sustained for at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
85
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 44 publications
15
85
2
1
Order By: Relevance
“…However, Craig and Jiang, et al, when doing treatment without MGE, also reported signi icant improvement in the qualitative component of the lipid layer, TFRT, and symptomatic scores [17]. Therefore, further studies with more signi icant sample numbers are needed to evaluate isolated IPL and compared it with MGE-associated IPL [12]. Comparing the success rate obtained in the eyelids, we found greater ef icacy of treatment in the lower eyelids.…”
Section: Treatment Eff Ectivenessmentioning
confidence: 66%
See 4 more Smart Citations
“…However, Craig and Jiang, et al, when doing treatment without MGE, also reported signi icant improvement in the qualitative component of the lipid layer, TFRT, and symptomatic scores [17]. Therefore, further studies with more signi icant sample numbers are needed to evaluate isolated IPL and compared it with MGE-associated IPL [12]. Comparing the success rate obtained in the eyelids, we found greater ef icacy of treatment in the lower eyelids.…”
Section: Treatment Eff Ectivenessmentioning
confidence: 66%
“…However, the irst prospective analysis article to quantify clinical improvements in signs and symptoms was that of Albietz, et al in 2017. While clinical signs improved after three sessions, symptoms only improved after six weeks of inal treatment [12]. Regardless, 85% of participants had improved subjective and objective measures of symptomatology.…”
Section: Treatment Eff Ectivenessmentioning
confidence: 92%
See 3 more Smart Citations